Predictive value of peri-chemotherapy hematological parameters for febrile neutropenia in patients with cancer - Jia, Hongyuan; Liang, Long; Chen, Xue; Zha, Wenzhong; Diao, Wei; Zhang, Wei (Frontiers in Oncology, 2024)
Objective The aim of this study was to compare hematological parameters pre- and early post-chemotherapy, and evaluate their values for predicting febrile neutropenia (FN). Methods Patients diagnosed with malignant solid tumors receiving chemotherapy were included. Blood cell counts peri-chemotherapy and clinical information were retrieved from the hospital information system. We used the least absolute shrinkage and selection operator (LASSO) method for variable selection and fitted selected variables to a logistic model. We assessed the performance of the prediction model by the area under the ROC curve. Results The study population consisted of 4,130 patients with common solid tumors receiving a three-week chemotherapy regimen in Sichuan Cancer Hospital from February 2019 to March 2022. In the FN group, change percentage of neutrophil count decreased less (−0.02, CI: −0.88 to 3.48 vs. −0.04, CI: −0.83 to 2.24). Among hematological parameters, lower post-chemotherapy lymphocyte count (OR 0.942, CI: 0.934–0.949), change percentage of platelet (OR 0.965, CI: 0.955–0.975) and higher change percentage of post-chemotherapy neutrophil count (OR 1.015, CI: 1.011–1.018), and pre-chemotherapy NLR (OR 1.002, CI: 1.002–1.002) predicted an increased risk of FN. These factors improved the predicting model based on clinical factors alone. The AUC of the combination model was 0.8275. Conclusion Peri-chemotherapy hematological markers improve the prediction of FN.